2015
DOI: 10.1371/journal.pone.0129854
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics Reveals Jasmonic Acid-Associated Metabolism Related to Cotton Fiber Initiation

Abstract: Analysis of mutants and gene expression patterns provides a powerful approach for investigating genes involved in key stages of plant fiber development. In this study, lintless-fuzzless XinWX and linted-fuzzless XinFLM with a single genetic locus difference for lint were used to identify differentially expressed genes. Scanning electron microscopy showed fiber initiation in XinFLM at 0 days post anthesis (DPA). Fiber transcriptional profiling of the lines at three initiation developmental stages (-1, 0, 1 DPA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 68 publications
3
22
0
Order By: Relevance
“…Interestingly, we observed that the expression of GhHDT1502, GhHDT1503, and GhHDT1504 gradually decreased with the different stages of cotton fiber development (0-25 DPA), suggesting the dynamic levels of histone acetylation mediated by G. hirsutum HDACs in cotton fiber development. Fiber development is also regulated by phytohormones, including abscisic acid, auxin, gibberellic acid, ethylene, and jasmonic acid [5,[43][44][45][46]. Phytohormones have been reported to alter the chromatin structure through the regulation of chromatin modifiers [47], suggesting a potential crosstalk between phytohormones and histone acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed that the expression of GhHDT1502, GhHDT1503, and GhHDT1504 gradually decreased with the different stages of cotton fiber development (0-25 DPA), suggesting the dynamic levels of histone acetylation mediated by G. hirsutum HDACs in cotton fiber development. Fiber development is also regulated by phytohormones, including abscisic acid, auxin, gibberellic acid, ethylene, and jasmonic acid [5,[43][44][45][46]. Phytohormones have been reported to alter the chromatin structure through the regulation of chromatin modifiers [47], suggesting a potential crosstalk between phytohormones and histone acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CAMTAs are known to interact with various phytohormones including ethylene 15 , ABA 19 , salicylic acid 21 , auxin 13 , and jasmonate 21 . These phytohormones also play critical roles in cotton fiber development 53 , 54 . Thus identification of genes belonging to these phytohormone categories in PCoEGs and NCoEGs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Also, JA-associated metabolism is related to cotton fiber initiation 59 . In our work, we found that most of the GhJAZ genes could be induced by JA in the ovules during fiber initiation.…”
Section: Discussionmentioning
confidence: 99%